Development of a new HPLC method for in vitro and in vivo studies of haloperidol in solid lipid nanoparticles - Mohd Yasir; Udai Vir Singh Sara; Iti Som (Universidade de São Paulo, 2017)
ABSTRACT A simple and sensitive HPLC method was developed and validated for the quantification of haloperidol in solid lipid nanoparticles (SLNs). The developed method was used for detection of shelf life of haloperidol in SLNs. Calibration curve of haloperidol was also constructed in rat plasma using loratidine as internal standard. In vivo studies were performed on rats and concentration of haloperidol in brain and blood was measured for the determination of various pharmacokinetic and hence brain targeting parameters. Chromatogram separation was achieved using C18 column as stationary phase. The mobile phase consisted of 100 mM/L potassium dihydrogen phosphate-acetonitrile-TEA (10:90:0.1, v/v/v) and the pH was adjusted with o-phosphoric acid to 3.5. Flow rate of mobile phase was 2 mL/minute and eluents were monitored at 230 nm using UV/VIS detector. The method was validated for linearity, precision, accuracy, reproducibility, limit of detection (LOD) and limit of quantification (LOQ). Linearity for haloperidol was in the range of 1-16 µg/mL. The value of LOD and LOQ was found to be 0.045 and 0.135 μg/mL respectively. The shelf life of SLNs formulation was found to be 2.31 years at 4 oC. Various parameters like drug targeting index (DTI), drug targeting efficiency (DTE) and nose-to-brain direct transport (DTP) were determined for HP-SLNs & HP-Sol administered intranasally to evaluate the extent of nose-to-brain delivery. The value of DTI, DTE and DTP for HP-SLNs was found to be 23.62, 2362.43 % and 95.77% while for HP-Sol, values were 11.28, 1128.61 % and 91.14 % respectively.